Evaluation of endothelial function in exogenous subclinical hyperthyroidism and the effect of treatment - Sayed Mohammad Hosseini; Elham Khosravi Bakhtyari; Kiyan Heshmat-Ghahdarijani; Noushin Khalili (Advanced Biomedical Research, 2016)
Background: Subclinical hyperthyroidism (SHy) is a widespread condition in which cardiovascular manifestations are frequently occur, but there is still a debate about the vascular responsiveness in it. Measuring flow-mediated dilation (FMD) and intimae-media thickness (IMT) are used to evaluate endothelial function in these patients. Materials and Methods: Twenty-five patients with a diagnosis of exogenous SHy and 25 full matched healthy subjects were enrolled. At first FMD of brachial artery and IMT of common carotid artery were obtained from all the participants. In the second phase, in the second phase of study, the dosage of levothyroxine was reduced at least 25% of prior dosage, and this was continued until thyroid stimulating hormone became normal range. Measuring FMD and IMT was repeated after this intervention in the case group. Results: The mean age of case and control groups were 38.48 ± 12.05 and 36.72 ± 11.15 years, respectively. The mean of FMD in healthy people was dramatically higher than the subclinical hyperthyroid patients (P < 0.001) but no statistically significant difference was found for IMT (P = 0.459). After intervention in the case group, FMD was meaningfully increased (P < 0.001) but IMT of common carotid artery was not considerably changed (P = 0.491). Conclusions: This study demonstrated that FMD decreased in exogenous subclinical hyperthyroid patients which could be partially restored by treatment. These findings suggest that treatment of subclinical hyperthyroid state could improve endothelial dysfunction and at the end decreased the cardiovascular complications.